Mood Disorders and How They are Related to Death Anxiety for Some Infirmaries in Baghdad (Medico Legal Update, 2021)
The subject of mood disorders and death anxiety in the elderly is considered one of the topics that havebeen addressed only slightly and in limited ways in relation to general trends and psychological research inother subjects in terms of quality and quantity. As well as if there is a statistically significant effect of sexvariables, the sample of the study consisted of all the elderly who were able to respond to the researcher,which amounted to (110) elderly people, including (65) males and (45) females. We collected demographicinformation about the elderly, as well as translating the mood disorders scale, as well as the arithmeticaverages, percentages, deviations and the Pearson correlation coefficient were used. To reach the results ofthe study, a number of results were reached. The suffering of elderly people living in nursing homes in thecapital, Baghdad, from a high level of mood disorders. The suffering of the elderly residing in the nursinghomes of the capital, Baghdad, from a moderate feeling in the level of death anxiety. There are statisticallysignificant differences at the level of (0.05) between the elderly on the measures of mood disorders and deathanxiety that are related to the gender variable and return to the benefit of females. There is no statisticallysignificant relationship between mood disorders and death anxiety among the study sample.